Close to the enemy [videorecording (DVD)] - Sturgess, Jim; Molina, Alfred, 1953-; Bassett, Angela (Acorn, 2016)
Intelligence officer Captain Callum Ferguson, is tasked by the army to ensure that a captured German scientist, Dieter, starts working for the British RAF on urgently developing the jet engine. With the background of the emerging Cold War, it's crucial for British national security that cutting-edge technology is made available to the armed forces as quickly as possible.